Effects of Overspeed or Overload Plyometric Training on Jump Height and Lifting Velocity - Stien, Nicolay; Strate, Morten; Andersen, Vidar; Saeterbakken, Atle Hole (Sports Medicine International Open, 2020)
The aim of this study was to examine the effects of overspeed or overload plyometric training on jump height and lifting velocity in resistance trained females without plyometric training experience. Fifty-six participants (age: 21.2±1.7 years; body mass: 65.1±8.2 kg; height: 168.0±5.9 cm) were randomly allocated to either an overspeed (n=18), overload (n=18), or passive control (n=16) group. The two training groups completed 18.7±1.7 sessions consisting of three different plyometric exercises with overspeed or overload over eight weeks. Apart from the external loading, the two training modalities were identical. Following the training period, the changes in the recorded variables were not significantly different from those in the control group, nor did the training groups differ from each other. The training groups improved peak and average lifting velocity in the 40 and 60% of body mass loading conditions (9.50–33.37%, p=<0.001–0.038), whereas only the average lifting velocity improved in the 80% of body mass loading condition (OS: 14.47%, p<0.001 and OL: 23.13%, p<0.001). No significant changes occurred in the control group (9.18–13.55%, P=0.062–0.980). Overspeed and overload plyometric training may be viable methods for improving lifting velocity, but not squat jump height, in a population without plyometric training experience.
Keywords: velocity; training; muscle thickness; testing